Reduced epithelial suppressor of cytokine signalling 1 in severe eosinophilic asthma. Issue 3 (23rd June 2016) - Doran, Emma; Choy, David F.; Shikotra, Aarti; Butler, Claire A.; O'Rourke, Declan M.; Johnston, James A.; Kissenpfennig, Adrien; Bradding, Peter; Arron, Joseph R.; Heaney, Liam G.
Severe asthma represents a major unmet clinical need. Eosinophilic inflammation persists in the airways of many patients with uncontrolled asthma, despite high-dose inhaled corticosteroid therapy. Suppressors of cytokine signalling (SOCS) are a family of molecules involved in the regulation of cytokine signalling via inhibition of the Janus kinase–signal transducers and activators of transcription pathway. We examined SOCS expression in the airways of asthma patients and investigated whether this is associated with persistent eosinophilia. Healthy controls, mild/moderate asthmatics and severe asthmatics were studied. Whole genome expression profiling, quantitative PCR and immunohistochemical analysis were used to examine expression of SOCS1, SOCS2 and SOCS3 in bronchial biopsies. Bronchial epithelial cells were utilised to examine the role of SOCS1 in regulating interleukin (IL)-13 signalling in vitro . SOCS1 gene expression was significantly lower in the airways of severe asthmatics compared with mild/moderate asthmatics, and was inversely associated with airway eosinophilia and other measures of T-helper type 2 (Th2) inflammation. Immunohistochemistry demonstrated SOCS1 was predominantly localised to the bronchial epithelium. SOCS1 overexpression inhibited IL-13-mediated chemokine ligand (CCL) 26 (eotaxin-3) mRNA expression in bronchial epithelial cells. Severe asthma patients with persistent airway eosinophilia and Th2 inflammation have reduced airway epithelial SOCS1 expression. SOCS1 inhibits epithelial IL-13 signalling, supporting its key role in regulating Th2-driven eosinophilia in severe asthma. Persistent airway eosinophilia/Th2 inflammation in severe asthma is linked to reduced epithelial SOCS1 expression http://ow.ly/Mlgl3001UMU